Heart disease dianosis system by applying case-based reasoning (CBR) - Siew Ching, Saw (2012)
This is project overview of Heart Disease Diagnosis System (HDDS) by applying Case-Based Reasoning (CBR) technique. Diagnosis of disease is a vital and intricate job in medicine.There are a lot of Artificial Intelligence (AI) techniques to determine diagnosis.After comparisons were made between those techniques,CBR is chosen to diagnose heart disease.System presented in Java to make it accessible for users like health professionals and doctors.The result of this designed system to diagnose the heart disease effectively.HDDS developed using Eclipse as main compiler, SQL as database development tool,and Java language as the programming language.HDDS used Rapid Application Development (RAD) methodology in order to keep system more systematic